Demo Masak Menu Tinggi Protein Hewani Untuk Cegah Stunting - Ravi Masitah; Novianty Novianty; Irzal Fanany; Pesona Dessritina; Defi Selvianita; Iken Rahma Mahesty (Jurnal Medika: Medika, 2026)
Stunting remains a public health challenge that requires appropriate interventions, one of which is increasing the consumption of animal protein. This community service activity aims to enhance the knowledge and skills of mothers with toddlers in preparing catfish as a local protein source to prevent stunting. The method used was participatory cooking demonstrations in Kelurahan 15 Ulu, Palembang, involving 25 mothers with toddlers. Activities included introducing the benefits of catfish, practicing making catfish nuggets and meatballs, and conducting interactive discussions. Evaluation results showed a significant increase in participants' understanding, with an average post-test score of 74.8 compared to a pre-test score of 53.6. About 72% of participants committed to making catfish nuggets because they are easy to prepare and liked by children. This activity successfully empowers mothers with toddlers through an enjoyable and practical educational approach, while also encouraging the use of local resources to improve family nutrition. Thus, the cooking demonstration approach has proven effective in educating the community while empowering them to participate independently in efforts to prevent stunting.